Antibacterial Activity of Methanol Extract from Gelam (Melaleuca leucadendra) Leaves Against Pathogenic Bacteria - Mariani, Yeni; Yusro, Fathul (Jurnal Biologi Tropis, 2025)
Escherichia coli and Staphylococcus aureus are bacteria causing contagious diseases. Both bacteria have shown high levels of antibiotic resistance, making them essential targets in searching for new antibacterial agents from natural sources such as medicinal plants. Gelam (Melaleuca leucadendra) is a promising medicinal plant to be a new antibacterial agent. This research aims to analyze the biological activity of the methanol extract of Gelam leaves (M. leucadendra) in inhibiting the growth of E. coli and S. aureus bacteria. The Gelam leaf extract was prepared by maceration process in 96% methanol solution (1:7 ratio). The antibacterial assay was conducted using the disc diffusion method on MHA (Muller-Hinton Agar) media. Four levels of methanol leaf extract concentration were used: 50, 100, 150, and 200 mg/ml. Methanol 96% was used as negative control and amoxicillin as positive control. The highest inhibition in both bacteria tested, 1.67 mm on E. coli bacteria and 6.26 mm on S. aureus bacteria.